Quantum dot phosphors CaS:Ce3+ and CaS:Pb2+, Mn2+ for improvements of white light-emitting diodes optic characteristics - Dieu An Nguyen Thi; My Hanh Nguyen Thi; Phuc Dang Huu (Institute of Advanced Engineering and Science, 2022)
The goal of this study is to discover a new method that uses standard phosphors and quantum dots to improve the lighting qualities and heat manipulation of white light-emitting diodes (WLEDs). Despite the popularity as a good ingredient that offers good color rendering properties, quantum dots (QDs) have not been widely employed in the fabrication of WLEDs, particularly, the utilization of QDs-phosphor-mixed nanocomposite is limited. We propose a unique packaging design based on the research’s experimental findings. The layer of nanocomposites consisting of QDs and phosphors is horizontally positioned to the WLED for optimal lighting and heating efficiency. This study simulated and used four distinguishing white LEDs forms: mono-layer phosphorus, two double-layer remote phosphors featuring yellowish-red and yellowish-green organizations, and a triple-layer phosphor. In terms of color rendering and luminous outputs, the triple-layer phosphor configuration outperforms the other implementations, as per the finding.